2003
DOI: 10.1271/bbb.67.627
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Extracellular β-Galactosidase Secreted by Supension Cultured Rice (Oryza sativaL.) Cells

Abstract: A b-galactosidase was puriˆed 1300-fold by lactosylSepharose 4B and Sephacryl S-200 column chromatographies from the cultured medium of a rice-cell suspension. The puriˆed enzyme appeared as 47 kD and 40 kD polypeptides on SDS-PAGE and had a speciˆc activity of 65.1 units W mg. Optimum activity was observed at pH 3.5 and 609 C. The enzyme released galactose from galactoxyloglucan and pectic galactans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The enzyme characterized in this study showed a pH optimum at 5.0, similar to the b-galactosidases from Sterigmatomyces elviae (Onishi & Tanaka 1995) and Helix aspersa liver (Barnett 1971) but different to the beta-galactosidases from chicken seminal plasma (3.4-4.0; Droba & Broba 1987) and suspension-cultured rice (Oryza sativa) cells (3.5; Kaneko & Kobayashi 2003). The similarity in the molecular weights determined by denaturing SDS-PAGE and native gel filtration suggests that b-galactosidase is likely to be monomeric, as found in human liver (Mutoh et al 1988) and Thermus sp.IB-21 (Kang et al 2005) beta-galactosidases.…”
Section: Biochemical Characterization Of B-galactosidasementioning
confidence: 48%
See 2 more Smart Citations
“…The enzyme characterized in this study showed a pH optimum at 5.0, similar to the b-galactosidases from Sterigmatomyces elviae (Onishi & Tanaka 1995) and Helix aspersa liver (Barnett 1971) but different to the beta-galactosidases from chicken seminal plasma (3.4-4.0; Droba & Broba 1987) and suspension-cultured rice (Oryza sativa) cells (3.5; Kaneko & Kobayashi 2003). The similarity in the molecular weights determined by denaturing SDS-PAGE and native gel filtration suggests that b-galactosidase is likely to be monomeric, as found in human liver (Mutoh et al 1988) and Thermus sp.IB-21 (Kang et al 2005) beta-galactosidases.…”
Section: Biochemical Characterization Of B-galactosidasementioning
confidence: 48%
“…Entomological Science (2007) 10, [343][344][345][346][347][348][349][350][351][352] for the beta-galactosidases from cold-adapted bacterium (26°C) (Fernandes et al 2002) and Aspergillus nidulans (30°C) (Diaz et al 1996), but it is lower when compared to those reported for beta-galactosidases from Kluyveromyces lactis (60°C; Ramirez & Rivas 2003) and Sterigmatomyces elviae (85°C; Onishi & Tanaka 1995). The enzyme characterized in this study showed a pH optimum at 5.0, similar to the b-galactosidases from Sterigmatomyces elviae (Onishi & Tanaka 1995) and Helix aspersa liver (Barnett 1971) but different to the beta-galactosidases from chicken seminal plasma (3.4-4.0;Droba & Broba 1987) and suspension-cultured rice (Oryza sativa) cells (3.5; Kaneko & Kobayashi 2003). The similarity in the molecular weights determined by denaturing SDS-PAGE and native gel filtration suggests that b-galactosidase is likely to be monomeric, as found in human liver (Mutoh et al 1988) and Thermus sp.IB-21 (Kang et al 2005) beta-galactosidases.…”
Section: Biochemical Characterization Of B-galactosidasementioning
confidence: 66%
See 1 more Smart Citation
“…1, B and G) could be due to one or more of the other 17 members of family 35 of glycosyl hydrolases (Ahn et al, 2007). A rice ortholog of AtBGAL8 had activity against both xyloglucan and galactans (Kaneko and Kobayashi, 2003). Similarly, a pea ortholog of AtBGAL16 could remove Gal from both xyloglucan and pectic polysaccharides (Dwevedi and Kayastha, 2009).…”
Section: Insertions Inmentioning
confidence: 99%
“…Konno and Tsumuki [ 36 ] identified both soluble and cell-wall-bound Bgal, of which a 42 kDa soluble Bgal was purified and shown to release galactose from larch wood and rice cell wall arabinogalactans. Likewise, Kaneko and Kobayashi [ 37 ] isolated a Bgal with 40 and 47 kDa subunits from the medium of rice suspension cells. Recently, Chantarangsee et al [ 38 ] characterized two recombinant Bgal isozymes, including the 90 kDa OsBgal1 and 72 kDa OsBgal2, which had different expression patterns, though both are found throughout plant growth.…”
Section: Introductionmentioning
confidence: 99%